SNP Genotyping by Multiplexed Solid-Phase Amplification and Fluorescent Minisequencing - Shapero, Michael H. (Cold Spring Harbor Laboratory Press, 2001)
The emerging role of single-nucleotide polymorphisms (SNPs) in clinical association and pharmacogenetic studies has created a need for high-throughput genotyping technologies. We describe a novel method for multiplexed genotyping of SNPs that employs PCR amplification on microspheres. Oligonucleotide PCR primers were designed for each polymorphic locus such that one of the primers contained a recognition site for BbvI (a type IIS restriction enzyme), followed by 11 nucleotides of locus-specific sequence, which reside immediately upstream of the polymorphic site. Following amplification, this configuration allows for any SNP to be exposed by BbvI digestion and interrogated via primer extension, four-color minisequencing. Primers containing 5′ acrylamide groups were attached covalently to the solid support through copolymerization into acrylamide beads. Highly multiplexed solid-phase amplification using human genomic DNA was demonstrated with 57 beads in a single reaction. Multiplexed amplification and minisequencing reactions using bead sets representing eight polymorphic loci were carried out with genomic DNA from eight individuals. Sixty-three of 64 genotypes were accurately determined by this method when compared to genotypes determined by restriction-enzyme digestion of PCR products. This method provides an accurate, robust approach toward multiplexed genotyping that may facilitate the use of SNPs in such diverse applications as pharmacogenetics and genome-wide association studies for complex genetic diseases.